2013
DOI: 10.1007/s00296-013-2696-1
|View full text |Cite|
|
Sign up to set email alerts
|

Folate usage in MTX-treated juvenile idiopathic arthritis (JIA) patients is inconsistent and highly variable

Abstract: Folate supplementation is widely accepted and utilized for the prevention of adverse events in juvenile idiopathic arthritis (JIA) patients who are treated with methotrexate. Despite the widespread use of folate supplementation, there is a lack of convincing evidence to support the role of folate in the enhancement of methotrexate efficacy and the prevention of methotrexate-related adverse events. In order to understand current practices used by experts, we surveyed 214 pediatric rheumatologists around the glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Nausea was already reported in the available literature on MTX in pediatric psoriasis (4)(5)(6), and also in other indications in children nausea is a wellknown side-effect (29,30). Possibly, different treatment schedules in folic acid administration can influence the presence of nausea and other AEs; the effect of different treatment schedules of folic acid administration on the effectiveness and side effects in MTX therapy is still subject of debate (8,31) and the use and dose regimen of folic acid administration is highly variable (32). In the pediatric psoriasis literature, tiredness was not reported until now, whereas in this study, it was reported as reason for discontinuation.…”
Section: Discussionmentioning
confidence: 95%
“…Nausea was already reported in the available literature on MTX in pediatric psoriasis (4)(5)(6), and also in other indications in children nausea is a wellknown side-effect (29,30). Possibly, different treatment schedules in folic acid administration can influence the presence of nausea and other AEs; the effect of different treatment schedules of folic acid administration on the effectiveness and side effects in MTX therapy is still subject of debate (8,31) and the use and dose regimen of folic acid administration is highly variable (32). In the pediatric psoriasis literature, tiredness was not reported until now, whereas in this study, it was reported as reason for discontinuation.…”
Section: Discussionmentioning
confidence: 95%
“…Our data show that higher dosage of folates may be beneficial in patients with MTX-related GI complaints and also the route of administration may be important, as in our patients the strategy of giving LVF before MTX might have contributed to effectiveness. Indeed, the optimal folate regimen is still matter of debate and there is great variability among clinicians on prevention and treatment of MTX-related side effects [ 9 , 20 ]. Therefore, further studies using LVF or FA before MTX since the start of the treatment should be performed to evaluate if this modality is effective also in preventing the development of adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, Arabelovic and associates' preliminary study showed a significant increase of MTX dose needed [ 114 ], since folic acid fortification enriched cereal grain products were fully implemented in the USA and Canada [ 115 ]. This conveyed a message to us that high dose of folate supplementation might have influence on the efficacy of MTX.…”
Section: The Side Effects Of Mtxmentioning
confidence: 99%